Governing New Guinea : an oral history of Papuan administrators, 1950-1990 - Visser, Leontine E. (KITLV Press, 2012)
This is the first time that indigenous Papuan administrators share with an international public their experiences governing their country. These administrators were the brokers of development. After graduating from the School for Indigenous Administrators (OSIBA) they served in the Dutch administration until 1962. The period 1962-1969 stands out as turbulent and dangerous, and for many curtailed their professional careers. These administrators' having been in active service until their retirement in the early 1990s allows for a complete recounting of political and administrative transformations under the Indonesian governance of Irian Jaya/Papua.This book brings together 17 oral histories of the everyday life of Papuan civil servants, including their relationships with superiors and colleagues, the murder of a Dutch administrator, their translation of 'development' to the Papuan people, the organization of their first democratic institutions, and the actual political and economic conditions leading up to the so-called Act of Free Choice. Finally, they share their experiences in the UNTEA and Indonesian government organization.Leontine Visser is Professor of Development Anthropology at Wageningen University. Her research focuses on governance and natural resources management in eastern Indonesia.